(3fRgI GdYjhf aj CQHYI afhfs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW , J (B718 (3g` s; (3eLghds ((3efUhQ Hf eMeO GdYHGOi s)
(3ChdgG (B:s
(3hHYO adJPcQ GdSeGA heG ChOYJ chGcHgG GdKGHJI hGdSGFQI s
(3BNQgG (B:s
(3acCf jhec ai ZdGdg aVI hGdfHJ ef PgH Ydi ajQhRL s
(3efGgL GdacQ jSei CjVkG (B" (3eHGgL GdacQ(B"s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B143s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B105 s
Keywords: (3GdeYGQa GdYGeIs